‘Around Us, History Never Stops’: Interrogating Post-quake Haiti in Évelyne Trouillot’s Absences sans Frontières - Carla Bascombe (Karib)
Immediately following the 2010 earthquake, Évelyne Trouillot imbued her corpus with what Rachel Douglas refers to as ‘archival impulses’ (Douglas, 2016: 389), in the form of op-eds, poetry, essays and short fiction. These ‘impulses’ were then further documented with the publication of 'Absences sans frontières' (Trouillot, 2013), a novel about post-quake Haiti. This article interrogates how Évelyne Trouillot uses 'Absences sans frontières' to interpret both the aesthetics of humanitarianism and the global political responses that emerged in the wake of the 2010 earthquake in Haiti. Informed by elements such as the evasive language of Trouillot’s narrator when reflecting upon the earthquake and the narrator’s father’s observations of Haiti-related media coverage in the United States, this article adopts a dual approach to examining 'Absences sans frontières'. In so doing, it identifies the narrative strategies employed by Trouillot that are used to invert the subjectivity of the earthquake victims/humanitarian workers paradigm. The novel is, in essence, a series of snapshots that provide alternative perspectives that humanise the victims of the tremor and challenge the motives of the humanitarian workers. To a lesser extent, the article equally considers the intrinsic relationship between humanitarianism and politics. It consequently analyses 'Absences sans frontières'’ nuanced perspective on the United States’ political reactions, which affected both Haitians within Haiti and the diaspora.